IECON 2018 - 44th Annual Conference of the IEEE Industrial Electronics Society 2018
DOI: 10.1109/iecon.2018.8591767
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Distributed Signal Processing Unit for Transmission Line Protection in a Centralized Substation Protection Architecture

Abstract: Travelling-wave and time-domain-based protection functions provide significant response time improvements over conventional phasor-based protection functions in power systems. These types of protection functions require very high sampling rates in the order of several hundreds of kHz. This paper proposes a novel centralized substation protection architecture (CPC) based on distributed signal processing units (DSPU) that enables the deployment of these high sampling rate applications in digital substations util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…, where the error δ s has been normalized to δ p,k by the weighting function in (19). This approach is performed for each subfilter k of the first L1 and second level of decimation L2.…”
Section: B Minimum Number Of Non-zero Coefficients and Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…, where the error δ s has been normalized to δ p,k by the weighting function in (19). This approach is performed for each subfilter k of the first L1 and second level of decimation L2.…”
Section: B Minimum Number Of Non-zero Coefficients and Lengthmentioning
confidence: 99%
“…Publishing those digitized signals with high sampling rates on switched Ethernet-based networks leads to a significant increase of the communication load. To mitigate these challenges, the authors of this paper have in [19], [20] proposed to compute the protection related signal features directly at the point of measurement in a device termed distributed signal processing unit (DSPU). The DSPU can be seen as a refinement of the SAMU.…”
Section: Introductionmentioning
confidence: 99%
“…For PMUs, the phase of the AA filter adds to the error of the instrument and needs to be characterized and corrected. When digital filters are used with oversampling ADCs, the group delay of these filters is a factor for measuring absolute phase in PMUs [11], [12].…”
Section: B Anti-aliasing Filtersmentioning
confidence: 99%
“…Only some studies have been found in the literature about this aspect. Reference [19] describes the design of a distributed signal processing unit (DSPU) applied to transmission line protection. The study extracts, from the analog signals measured in the substation bay, the information used by protection functions such as harmonics, interharmonics,... Once this information is obtained, it is encoded and published via the IEC 61850 GOOSE communication service.…”
Section: Introductionmentioning
confidence: 99%
“…CPC subscribes to this information and performs the corresponding protection and control functions. The solution proposed in [19] does not consider how issues in communication channels, such as loss of packets and delays, can affect the operation of protection functions implemented in CPC. Furthermore, this solution involves specific hardware for its implementation.…”
Section: Introductionmentioning
confidence: 99%